Evolutionary origin of Hoxc13-dependent skin appendages in amphibians - Marjolein Carron; Attila Placido Sachslehner; Munevver Burcu Cicekdal; Inge Bruggeman; Suzan Demuynck; Bahar Golabi; Elfride De Baere; Wim Declercq; Erwin Tschachler; Kris Vleminckx; Leopold Eckhart (Nature Communications, 2024)
Abstract Cornified skin appendages, such as hair and nails, are major evolutionary innovations of terrestrial vertebrates. Human hair and nails consist largely of special intermediate filament proteins, known as hair keratins, which are expressed under the control of the transcription factor Hoxc13. Here, we show that the cornified claws of Xenopus frogs contain homologs of hair keratins and the genes encoding these keratins are flanked by promoters in which binding sites of Hoxc13 are conserved. Furthermore, these keratins and Hoxc13 are co-expressed in the claw-forming epithelium of frog toe tips. Upon deletion of hoxc13, the expression of hair keratin homologs is abolished and the development of cornified claws is abrogated in X. tropicalis. These results indicate that Hoxc13-dependent expression of hair keratin homologs evolved already in stem tetrapods, presumably as a mechanism for protecting toe tips, and that this ancestral genetic program was coopted to the growth of hair in mammals.